2013
DOI: 10.1111/irv.12093
|View full text |Cite
|
Sign up to set email alerts
|

The first, second and third wave of pandemic influenza A (H1N1)pdm09 in North Denmark Region 2009–2011: a population‐based study of hospitalizations

Abstract: Background and objectivesDenmark experienced three waves of the new pandemic influenza A (H1N1)pdm09 from July 2009 to February 2011. The aim of the study was to describe the epidemiology and clinical characteristics of hospitalized patients in a defined population of North Denmark Region with a mixed urban and rural community of 579 000 inhabitants.MethodsReview of medical records of all hospitalized patients with confirmed influenza A from July 2009 to February 2011.ResultsTwo hundred and seventy‐three patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
5
12
1
Order By: Relevance
“…In The Australian and New Zealand Intensive Care (ANZIC) study, from June 1–August 31, 2009, a total of 28.7 cases/1 million inhabitants were admitted to the ICUs of Australia and New Zealand ( 7 ). A population study in Denmark found 9 (5.69%) of 158 patients were admitted to a hospital ICU during the second wave of the 2009 influenza pandemic ( 8 ), compared with ≈7.6% (≈13/171) in this study. …”
Section: Discussioncontrasting
confidence: 62%
“…In The Australian and New Zealand Intensive Care (ANZIC) study, from June 1–August 31, 2009, a total of 28.7 cases/1 million inhabitants were admitted to the ICUs of Australia and New Zealand ( 7 ). A population study in Denmark found 9 (5.69%) of 158 patients were admitted to a hospital ICU during the second wave of the 2009 influenza pandemic ( 8 ), compared with ≈7.6% (≈13/171) in this study. …”
Section: Discussioncontrasting
confidence: 62%
“…83,92 were excluded from the meta-analysis because one was only a synopsis 83 and one compared zanamivir to usual care and not placebo. 92 We finally included 26 zanamivir trials: 14 on treatment in adults, [71][72][73]77,[80][81][82]87,89,91,95,[97][98][99] two in children 78,84 and 10 trials in prophylaxis. 70,79,85,86,88,90,93,94,96,100 Our attempt at collecting sufficient information from regulatory files to reconstruct missing CSRs also failed because the information appeared to be insufficient for a reliable reconstruction.…”
Section: Zanamivirmentioning
confidence: 99%
“…In two zanamivir adult trials, 81,82 pneumonia reporting was based on a stricter definition of X-ray confirmation and there was also no significant treatment effect (RR 1.02, 95% CI 0.35 to 3.02; I 2 statistic = 39%). In nine zanamivir trials, 77,79,80,87,89,91,[97][98][99] pneumonia was a self-reported, investigator-mediated, unverified outcome (see Figures 8 and 9). Overall, there was no significant effect of zanamivir on mixed verified and unverified pneumonia in adult treatment (RR 0.90, 95% CI 0.58 to 1.40; I 2 statistic = 0%).…”
Section: Pneumoniamentioning
confidence: 99%
“…1 shows the temporal distribution of severely ill patients with laboratory confirmed influenza A(H1N1)pdm09 infection admitted to hospitals and the average daily number of attendances for ARI at government primary care clinics from epidemiological week (Eweek) 23 (7)(8)(9)(10)(11)(12)(13) in 2009 to E-week 32 (6)(7)(8)(9)(10)(11)(12) in 2010. In 2009, a steady increase in attendances for ARI was observed from E-week 25 (21)(22)(23)(24)(25)(26)(27) onwards, which peaked in E-week 30 (26 July-1 August), and decreased over the subsequent weeks until E-week 36 (6)(7)(8)(9)(10)(11)(12).…”
Section: Definition Of Time Periodsmentioning
confidence: 99%
“…A study conducted in England reported a greater burden of severe illness with more deaths, more critical care admissions and more hospital admissions due to influenza A(H1N1)pdm09 in the second year of its circulation than in the pandemic year [23]. A population-based study of hospitalisations in Northern Denmark Region also found that in comparison with the pandemic wave, the severity of hospitalised patients and requirement for ICU admission increased in the post-pandemic wave [24]. Similarly, a retrospective cohort study of all patients with laboratory-confirmed influenza A(H1N1)pdm09 infection admitted to a hospital in Heidelberg, Germany, from May 2009 to April 2011 found increased proportion of patients with severe disease and fatal cases in the post-pandemic season [10].…”
Section: Tablementioning
confidence: 99%